Recurrent encapsulation after Ahmed glaucoma valve implantation in a patient with Schwartz–Matsuo syndrome - Ana Rita Viana; Ricardo Bastos; Carolina Vale; Paula Tenedório (The Pan-American Journal of Ophthalmology)
Glaucoma drainage devices (GDDs) are an important tool for the treatment of complicated/refractory glaucoma cases. Excessive capsular fibrosis is a frequent cause of long-term failure of Ahmed® glaucoma valve (AGV) that is difficult to manage and often requires additional surgical interventions. We describe a severe case of recurrent encapsulation and restrictive strabismus following AGV implantation in a young man with Schwartz–Matsuo syndrome. The patient underwent a first surgical revision that consisted of the excision of the fibrous capsule. However, a second intervention was soon needed, in which the fibrous capsule and the AGV were removed, and an Ahmed ClearPath® was implanted in the nasal-inferior quadrant. The ocular movements were successfully restored and the intraocular pressure was well controlled. GDDs can fail due to excessive wound healing and fibrosis around the plate. Severe cases occur more often in young patients. Ahmed ClearPath® can be a good option for eyes more prone to complications.